Tradução, adaptação transcultural e validação de um protocolo de cuidados para pacientes com constipação intestinal - Shimazaki, Marcela Reis Pedrasini (2021)
The bowel constipation is one of the functional diseases which affect the bowel, and it’s one of the most prevalent complains in the medical care. Approximately 20% of the world population report this symptom, with higher prevalence in women and elderly. The chronic constipation care is an important public health problem, due to its high prevalence and lack of specialized care. The objective of this study was to translate to the Brazilian Portuguese language, make the transcultural adaptation, and validate the care program protocol for patients with bowel constipation, elaborated by Christine Norton et al for research and treatment use in Brazil; apply and evaluate the efficacy of using the protocol in the bowel constipation treatment. It’s a study of translation, transcultural adaptation and validation. The following steps were performed: the translation processes, synthesis of the translations, back-translations, synthesis of the back-translations and submission to the judges committee. The conceptual, cultural, idiomatic and semantic equivalences were evaluated by five judges specialists, and consolidated by the Content Validity Index (CVI), with final result CVI = 1. The final version of the Habit Training Interventions Protocol was applied to 30 participants with bowel constipation, during a 60 days period. Results: after the protocol application, there was a significant improvement in the evacuations frequency as well as in the faeces consistency. The conclusion was that the use of a standardized and validated tool as the Habit Training Interventions Protocol for bowel constipation can help the health care professionals in the non medicamentous approach to manage the patients who suffer with constipation